GATA3 maintains the quiescent state of cochlear supporting cells by regulating p27kip1 - Jiadong Xu (Nature Portfolio, 2021)
Abstract Haplo-insufficiency of the GATA3 gene causes hypoparathyroidism, sensorineural hearing loss, and renal disease (HDR) syndrome. Previous studies have shown that Gata3 is required for the development of the prosensory domain and spiral ganglion neurons (SGNs) of the mouse cochlea during embryogenesis. However, its role in supporting cells (SCs) after cell fate specification is largely unknown. In this study, we used tamoxifen-inducible Sox2 CreERT2 mice to delete Gata3 in SCs of the neonatal mouse cochlea and showed that loss of Gata3 resulted in the proliferation of SCs, including the inner pillar cells (IPCs), inner border cells (IBCs), and lateral greater epithelium ridge (GER). In addition, loss of Gata3 resulted in the down-regulation of p27kip1, a cell cycle inhibitor, in the SCs of Gata3-CKO neonatal cochleae. Chromatin immunoprecipitation analysis revealed that GATA3 directly binds to p27 kip1 promoter and could maintain the quiescent state of cochlear SCs by regulating p27 kip1 expression. Furthermore, RNA-seq analysis revealed that loss of Gata3 function resulted in the change in the expression of genes essential for the development and function of cochlear SCs, including Tectb, Cyp26b1, Slitrk6, Ano1, and Aqp4.